MAGNETIC ANALYSIS OF FRACTIONAL SLOT PERMANENT MAGNET SYCHRONOUS MACHINE - Oner, Yasemin; Senol, Ibrahim; Bekiroglu, Nur; Aycicek, Engin (YILDIZ TECHNICAL UNIV, 2012)
In this article, analytical method is used in pmsm design and the effects of geometric quantities on the performance of the machine is pointed out. Magnetic equivalent circuit (MEC) model is used as numeric method. It is observed that the composed MEC model is coherent to Analytical model. Composed model is applied on fractional permanent magnet synchronous machines.
Keywords: Machine design; magnetic analysis; analytical model; permanent magnet synchronous machine; Engineering